The Effects of Moringa oleifera Leaves on Complete Blood Count, Renal and Liver Functions as Potential Therapy for Malnutrition - Gamar Musa Kodi; Howeida Abdullah Mustafa; Alkhair Abd Almahmoud Idris (Cell and BioPharmaceutical Institute, 2022)
Background: Moringa oleifera which is available in many areas all over the world including Sudan is low-cost and traditionally used in the treatment of many disorders, including malnutrition. This study aimed to determine the effect of aqueous extract of M. oleifera leaves in renal, liver functions and complete blood count (CBC) parameters, and its potential as therapy for malnutrition.Materials and methods: This was an experimental case control study using twenty-five Wistar albino rats. Rats were divided into three groups: normal protein diet group, low protein diet with or without M. oleifera extract groups. We determined rats' weight, CBC parameters, blood mineral concentrations, as well as liver and renal functions at day 0, 7, and 14.Results: Our findings showed that rats' weight were significantly different between the three groups at day 0, 7, and 14. Rats' weight, blood sodium, potassium, calcium, and urea concentration, as well as Hb concentration, TWBCs count, total platelets count, and %lymphocyte showed significant differences between three groups at day 0, 7, and 14.Conclusion: M. oleifera leaves can be used as potential therapy for malnutrition because they have some effects on weight, blood mineral concentrations, renal and liver function, as well as CBC parameters.Keywords: ALP, AST, ALT, creatinine, Moringa oleifera